Investigation of the mechanism of Isobavachalcone in treating rheumatoid arthritis through a combination strategy of network pharmacology and experimental verification. (10th August 2022) - Wang, Shaohui; Du, Qinyun; Sun, Jiayi; Geng, Sang; Zhang, Yi
Abstract: Ethnopharmacology relevance: Isobavachalcone (IBC) is a natural chalcone compound widely distributed in traditional Chinese medicine Psoralea corylifolia L., and Tibetan medicine Abelmoschus manihot (L.) Medik. Etc.. Among them, Psoralea corylifolia has the effect of tonifying the kidney and strengthening Yang, and it is recorded in the Medicinal theory that it can be used in managing rheumatism and arthralgia. In addition, It has been included in many prescriptions in traditional Chinese medicine as the main herb for managing rheumatoid arthritis (RA). Similarly, Abelmoschus manihot is a common Tibetan medicinal herb and is a common medicinal material in Tibetan medicine and reported in ancient medicinal books such as Jing Zhu Ben Cao and Si Bu Yi Dian to possess the effect of Ganhuangshui and thus can be used in treating Huangshui diseases (such as RA). Previous research has demonstrated IBC to possess numerous biological activities, including anti-cancer, anti-inflammatory, antibacterial and immunomodulatory. Nevertheless, its efficacy and potential mechanism in treating rheumatoid arthritis are yet to be investigated. Aim of the study: This study aimed at investigating the therapeutic efficacy and mechanism of IBC in treating RA through a combined strategy of network pharmacology, in vitro, and in vivo evaluation. Materials and methods: The Swiss Target Prediction and GeneCards databases were consulted to predict the potential targets of IBC and RA. Additionally, the potential targets for IBC in treating RA were predicted by consulting databases such as String, Cytoscape, MCODE, and Cytohubba. R software was utilized for enrichment analysis of GO and KEGG pathways, followed by in vitro experimentation using cell lines and in vivo experimentation using animals to explore the potential mechanism of IBC in RA treatment. Results: By integrating the results of network pharmacological analysis, 17 genes were found to be strongly associated with RA, such as TNF, MAPK13, EGFR, PTGS2, MMP3, etc. The enrichment analysis indicated that IBC possessed tremendous therapeutic efficacy in managing RA through PI3K-AKT, rheumatoid arthritis, and TNF signaling pathways. The in vitro experimentation indicated that IBC inhibited the proliferation, migration, and invasion, and promoted apoptosis and inhibition of inflammation of MH7A cell lines stimulated with TNF-α. The IBC might also have an increasing effect on the intracellular ROS and reducing effect on the mitochondrial membrane potential. The western blotting results indicated that IBC markedly inhibited the expression of p-PI3K, p-AKT, p-JAK1, p-STAT3 and SOCS3 proteins in TNF-α stimulated MH7A cells. Furthermore, we found that IBC also significantly reduced paw swelling and arthritis severity in CIA model rats through in vivo animal studies. Conclusions: In short, this study explored the effect of IBC by combining network pharmacology prediction with in vitro and in vivo experimentation. The results indicated that IBC exerts its anti-rheumatoid arthritis effect by regulating cell proliferation and survival via PI3K/AKT and JAK/STAT signaling pathways. This may open a new horizon and provide a theoretical foundation for further development and utilization of IBC in RA management. Graphical abstract: Image 1 Highlights: Network pharmacology and experimental validation strategies could well reveal the potential anti-RA mechanism of Isobavachalcone. Isobavachalcone from multiple medicinal plant sources showed strong potential anti-RA activity in vitro and in vivo. Isobavachalcone exerted its anti-RA effect mainly via the PI3K/AKT and JAK/STAT signaling pathways.